Analisa Pelaksanaan Audit Lingkungan pada Industri Plastik Kemasan di PT. Emblem Asia - Yudia Ihsanat Sudibjo; Sintorini Moerdjoko; Endro Suswantoro (Publikasi Indonesia, 2022)
Emblem Asia is a plastic manufacturing company that is located in Karawang Industrial Area MM2100 Cikarang. The objective of this research is to analyze the implementation of environmental management system ISO 14001:2015 that is done by the company. The research was carried out in the period of February –July 2022. The analysis uses quantitative methods which focuses on gap analysis method. A questionnaire with 31 questions about employe performance regarding EMS implementation, which where arranged trough validity and reliability tests, was addressed trough the respondents for research purposes. For the calculation of gap analysis, the questionnaires where distributed to 31 respondents from various levels of office, which results in 20% gap. From the results of this study, it can be concluded that implementation of EMS in PT. Emblem asia was monitored according to the international standards for ISO 14001. Suggestions to improve the performance of implementing EMS ISO 14001:2015 are to maintain everything that has been achived in implementing EMS ISO 14001:2015.